Different factors drive the assembly of pine and Panax notoginseng-associated microbiomes in Panax notoginseng-pine agroforestry systems - Jia, Weijia; Wang, Shu; He, Xiahong; Zhao, Xiaoyan (Frontiers in Microbiology, 2022)
The composition and assembly of plant-associated microorganisms may be influenced by land-use conversion, which in turn affects plant growth, development, and ecosystem functioning. Agroforestry systems, as one of the ecological practices to mitigate arable land stress and climate change, have received little attention regarding the dynamics of different plant-associated microbes within their systems. In this study, we used high-throughput sequencing technology to analyze the assembly mechanisms of pine-related microbes during the conversion of pine forests into Panax notoginseng (P.n.)-pine agroforestry systems. Additionally, the effects of different pine species on P.n.-associated microorganisms under the P.n.-pine agroforestry systems were compared and analyzed to systematically show the changes and assembly mechanisms of different plant-associated microorganisms under the P.n.-pine agroforestry systems. The results showed that pure pine forest conversion into P.n.-pine agroforestry systems significantly altered the diversity of pine fungi rather than the community structure. The community structure of P.n.-associated fungi was significantly altered under different pine species of P.n.-pine agroforestry systems, rather than diversity. Plant-associated fungi were more responsive to land-use change than bacteria. In addition, the hierarchical filtering effect of plants was different in pine and P.n. In agroforestry systems, there was a transfer of P.n. endophytes to pine trees. The different assembly patterns of pine and P.n.-associated microorganisms reflect the complex plant-microbial-plant interactions in agroforestry ecosystems.